Optimization method of Al2O3 / Al2O3 composite material preparation process based on damage mechanism model
Through the preparation process based on the damage mechanism model, the preparation conditions of Al2O3/Al2O3 composite materials are optimized by acoustic and optical lossless methods, and the problems of experimental complexity and resource waste in the prior art are solved, and efficient and reliable composite materials are achieved. R&D.
Patent Information
- Application Number
- CN202411124430.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-17
AI Technical Summary
When studying the damage mechanism of Al2O3/Al2O3 composite materials in the prior art, the difference in raw materials causes the experiment to fail to reproduce the same performance. Preparing new components requires repeated testing under different experimental conditions, which is time-consuming and wasteful, and the preparation process is cumbersome and difficult to efficiently Research and develop new materials.
Using a preparation process based on the damage mechanism model, time-synchronized data is obtained through acoustic and optical lossless methods, a high-reliable damage mechanism model is established, the preparation conditions are optimized, the number of experiments is reduced, and the result reliability is improved.
It achieves reliable results that require only one experiment, shortens the exploration cycle of optimal preparation conditions, accelerates the output process of high-performance composite materials, improves R&D efficiency, and saves experimental costs.
Smart Images

Figure CN119152992A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material preparation, and in particular to an Al 2 O 3 / Al 2 O 3 Optimization method for composite material preparation process. Background Art
[0002] As a highly anticipated solution, continuous ceramic fiber reinforced ceramic matrix composites (CFRCMCs) have significantly improved the defects of single ceramics in terms of brittleness and reliability, and improved their damage tolerance. At the same time, CFRCMCs have the high strength, high hardness, wear resistance and corrosion resistance unique to single ceramics. 2 O 3 / Al 2 O 3 ) Composite materials broadly refer to ceramic matrix composite materials composed of continuous fibers and matrix with alumina as the main component. It has become an important branch in the field of continuous ceramic fiber toughened ceramic matrix composite materials. 2 O 3 / Al 2 O 3 Composite materials show significant advantages under complex working conditions such as high temperature, high oxygen, rich water vapor and medium load, so they have broad application prospects in aero engines, ground gas turbines, civil industry and other fields. 2 O 3 Basic research on fibers and composite materials is key to subsequent high-performance applications.
[0003] Composite materials have microscopic and macroscopic multi-scale characteristics, which make their mechanical behavior, especially their damage behavior, complex. The combination of different materials often presents failure modes such as delamination, cracking, debonding, and fiber breakage in different degrees and spaces, and different failure forms under different load conditions.
[0004] At present, the existing technology studies Al 2 O 3 / Al 2 O 3 The damage mechanism of composite materials is often difficult to reproduce with existing experimental methods due to the differences in the raw materials used. At the same time, when the raw material prices are high, the preparation of new Al 2 O 3 / Al 2 O 3 Composite materials need to be continuously prepared and tested under different experimental conditions until an optimal component and experimental condition are found.
[0005] This test method is time-consuming and requires a large investment of resources. In the process of preparing composite materials, the preparation and experimental conditions are complicated, there are many steps, and there are many parameters that need to be controlled. If the parameters are slightly changed, the results will be very different. When preparing samples under more conditions, it is time-consuming to perform all microscopic and macroscopic characterization experiments to verify the feasibility of the preparation conditions, which makes it impossible to efficiently develop new materials; if only one characterization method is used, the scientificity and reliability of the results cannot be guaranteed. Summary of the invention
[0006] In view of the above problems, the present invention provides an Al 2 O 3 / Al 2 O 3 The present invention is a method for optimizing the preparation process of composite materials. The invention establishes a highly reliable damage mechanism model, and only one experiment is required to obtain reliable results. Screening based on the fundamental damage mechanism of the material is conducive to the preparation of Al2O3 composite materials with excellent mechanical properties. 2 O 3 / Al 2 O 3 Composite materials; Time-synchronized data obtained by acoustic and optical non-destructive methods for cross-validation and interpretation of information related to materials and / or their structural integrity, thereby improving the reliability of measurements recorded independently by acoustic emission (AE) and DIC strain systems and avoiding misinterpretation of experimental results due to the chance of a single experiment.
[0007] The present invention provides an Al based damage mechanism model 2 O 3 / Al 2 O 3 The optimization method of composite material preparation process includes:
[0008] S1. Set preparation conditions, and prepare Al according to the preparation conditions. 2 O 3 / Al 2 O 3 Composite materials;
[0009] S2, using the synchronous test system to test the A1 in step S1 2 O 3 / Al 2 O 3 The composite material is subjected to tensile test, and the acoustic emission signal and strain data are collected to obtain the corresponding acoustic emission signal cluster analysis results and strain analysis results;
[0010] S3, establishing a damage mechanism model; judging the acoustic emission signal cluster analysis results and the strain analysis results in step S2 according to the damage mechanism model to obtain a judgment result;
[0011] S4. Optimize the preparation conditions of step S1 according to the judgment result and the damage mechanism model.
[0012] Preferably, the preparation of Al in step S1 2 O 3 / Al 2 O 3 The specific steps of composite materials include:
[0013] Step S11, mixing aluminum oxide powder and deionized water, adding nitric acid, and then using a ball mill to disperse the mixture to obtain a matrix solution;
[0014] Step S12, pre-impregnating the alumina fiber cloth in the matrix solution under vacuum conditions to obtain a prepreg;
[0015] Step S13, hot pressing the prepreg under vacuum conditions to obtain a preform;
[0016] Step S14: sintering the preform to obtain the first processed Al 2 O 3 / Al 2 O 3 Composite materials;
[0017] Step S14, let t=1, t=1 indicates the first processing; t is an integer;
[0018] Step S15: Under vacuum conditions, the Al 2 O 3 / Al 2 O 3 Composite material A t Pre-impregnated in the matrix solution in step S11 to obtain a pre-impregnated body S t ;
[0019] Step S16: Under vacuum conditions, the prepreg S t Perform hot pressing and drying to obtain preform Y t ;
[0020] Step S17: t Sintering is performed to obtain the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 ;
[0021] Step S18: Determine the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 Is the mass growth of ≤1%? If so, terminate the processing and obtain the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 ; If not, set t=t+1 and return to step S15.
[0022] Furthermore, the preparation conditions in step S1 include ball milling conditions, processing times, drying temperature of hot pressing, drying time of hot pressing, sintering temperature and / or sintering time;
[0023] Furthermore, the rotation speed of the ball mill is: 200-800r / h;
[0024] Furthermore, the mass ratio of the nitric acid to the alumina powder is: 0.3:40-70;
[0025] Furthermore, the mass percentage of nitric acid in step S11 is 0.3wt%;
[0026] The mass percentage of aluminum oxide powder is: 40-70wt%;
[0027] Further, the ratio of the drying temperature in step S13 to the sintering temperature in step S14 is: 12-15:100-120;
[0028] The ratio of the pre-impregnation time in step S12, the drying time in step S13 and the sintering time in step S14 is: 4-6:2-3:1;
[0029] Furthermore, the drying temperature of the hot pressing molding in step S13 is 120-150° C. and the drying time is 2-3 hours;
[0030] Furthermore, the pre-immersion time in step S12 is 4-6 hours;
[0031] The sintering temperature in step S14 is 1000-1200° C. and the sintering time is 1 hour.
[0032] The Al prepared in step S1 of the present invention 2 O 3 / Al 2 O 3 The composite material has uniform composition, excellent tensile properties, excellent morphology, and a controllable and simple preparation method, which is conducive to repeated tensile experiments.
[0033] Preferably, the synchronous testing system in step S2 includes a mechanical stretching machine, an acoustic emission testing system and a DIC system;
[0034] Furthermore, the synchronous testing system in step S2 further includes a computer;
[0035] The mechanical stretching machine, the acoustic emission test system and the DIC strain system are respectively connected to a computer; when the synchronous test system performs a tensile test on the sample, the evolution law of the acoustic emission signal over time and the evolution information of the DIC strain field over time and the stress-strain curve are synchronously recorded;
[0036] The mechanical stretching machine is used to apply a tensile load and record the tensile load and displacement data during the test;
[0037] The acoustic emission test system is used to obtain acoustic emission signals during the test and perform acoustic emission parameter analysis;
[0038] Furthermore, the DIC strain system is used to obtain the evolution information of the material surface strain field during the test process; the DIC system includes a strain gauge for recording strain data.
[0039] The present invention uses time synchronization of data obtained by acoustic and optical non-destructive methods to cross-validate and interpret information related to materials and / or the structural integrity of materials, thereby improving the reliability of measurements independently recorded by two systems, acoustic emission (AE) and DIC strain systems, avoiding comparison based on only one experimental result, thereby avoiding misjudgment of experimental results due to the contingency brought about by a single experiment.
[0040] Preferably, the specific steps of obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results in step S2 include:
[0041] Use the synchronous test system to test the Al in step S1 2 O 3 / Al 2 O 3 The composite material is subjected to a tensile test. During the tensile process, acoustic emission signals are collected and DIC strain fields are photographed. Acoustic emission signals and strain data are collected at the same time. After the tensile test, corresponding acoustic emission signal cluster analysis results and strain analysis results are obtained based on the collected acoustic emission signals and strain data.
[0042] Furthermore, the acoustic emission signal cluster analysis result in step S2 includes: stage signal one, stage signal two, stage signal three and stage signal four.
[0043] Further, in step S2, the synchronous test system is used to test the A1 in step S1. 2 O3 / Al 2 O 3 The specific steps of conducting a tensile test on a composite material, collecting acoustic emission signals and strain data, and obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results include:
[0044] Step 1. Set the stretching rate, and use the synchronous testing system to test the Al 2 O 3 / Al 2 O 3 The composite material is stretched, and the composite material is subjected to elastic deformation, and a stage signal 1 is obtained; based on the stage signal 1, an acoustic emission cumulative energy 1 and a stage 1 DIC strain distribution are obtained;
[0045] The stage signal 1 includes an acoustic emission signal 1;
[0046] When the composite material undergoes elastic deformation, the acoustic emission signal 1 appears as a no-acoustic emission signal; the acoustic emission cumulative energy 1 corresponding to the no-acoustic emission signal is almost 0;
[0047] Step 2. Based on step 1, 2 O 3 / Al 2 O 3 The composite material continues to stretch, Al 2 O 3 / Al 2 O 3 The matrix of the composite material is damaged and the fiber slips, and a second stage signal is obtained; based on the corresponding second stage signal, the second acoustic emission cumulative energy and the second stage DIC strain distribution are obtained;
[0048] The second stage signal includes the first acoustic emission signal and / or the second acoustic emission signal.
[0049] The acoustic emission signal 1 is manifested as matrix cracking; the acoustic emission signal 2 is manifested as fiber debonding;
[0050] Step 3. Based on step 2, 2 O 3 / Al 2 O 3 The composite material continues to be stretched to obtain a corresponding stage signal three; based on the stage signal three, the acoustic emission cumulative energy three and the stage three DIC strain distribution are obtained;
[0051] The stage signal three includes the acoustic emission signal one and / or the acoustic emission signal two and / or the acoustic emission signal three; the acoustic emission signal three is manifested as a single fiber break;
[0052] Step 4. Based on step 3, 2 O 3 / Al 2 O 3 The composite material continues to be stretched to obtain a corresponding stage signal four; based on the stage signal four, the acoustic emission cumulative energy four and the stage four DIC strain distribution are obtained;
[0053] The stage signal four includes the acoustic emission signal one and / or the acoustic emission signal two and / or the acoustic emission signal three and / or the acoustic emission signal four; the acoustic emission signal four indicates the breakage of the fiber bundle;
[0054] Preferably, the establishment of the damage mechanism model in step S3 specifically includes: 2 O 3 / Al 2 O 3 The damage mechanism model is established based on the acoustic emission signal and DIC strain field changes corresponding to the idealized process of composite material damage.
[0055] Preferably, the damage mechanism model described in step S3 specifically includes: collecting Al 2 O 3 / Al 2 O 3 Acoustic emission signals and strain data during tensile tests of composite materials are obtained to obtain corresponding acoustic emission signal cluster analysis results and strain analysis results; further, the damage mechanism model described in step S3 includes: stage one, acoustic emission cumulative energy one appears, the acoustic emission cumulative energy one is normalized, and the DIC strain field shows a uniform strain distribution;
[0056] It can be understood that the stage 1 specifically includes: obtaining the acoustic emission cumulative energy 1 according to the received acoustic emission signal 1. Since the composite material is in the elastic deformation stage and is almost undamaged, the corresponding acoustic emission cumulative energy 1 is very low. At the same time, the DIC strain field exhibits a uniform strain distribution;
[0057] In stage 2, the acoustic emission cumulative energy 2 appears and begins to increase, and at the same time, the corresponding DIC strain bands no longer show uniform strain bands;
[0058] In stage three, the acoustic emission cumulative energy 2 continues to increase to its corresponding boundary point, and the acoustic emission cumulative energy 3 appears. The acoustic emission cumulative energy 3 begins to climb and enters the high strain stage, and a stress concentration point appears in the DIC strain field;
[0059] Furthermore, the stage three also includes the acoustic emission cumulative energy three and the acoustic emission signal two synchronously rising in a fluctuating manner;
[0060] In stage four, the acoustic emission cumulative energy three climbs to the corresponding boundary point, and a failure point appears. After a certain period of time, the acoustic emission signal two caused by fiber pull-out appears, and the acoustic emission cumulative energy four corresponding to it continues to increase, and the DIC stress concentration point continues to expand until it is destroyed.
[0061] It can be understood that the cumulative acoustic emission energy of the composite material is at the beginning of stretching. According to the elasticity of the composite material itself, the composite material at the current stage has no damage, and the corresponding cumulative acoustic emission energy is almost 0;
[0062] The second acoustic emission cumulative energy is that the composite material is continuously stretched, and the composite material begins to break the matrix and the fibers begin to debond, and the corresponding second acoustic emission cumulative energy begins to increase;
[0063] The acoustic emission cumulative energy three is to continue to stretch the composite material. When the acoustic emission cumulative energy two reaches a certain critical point, the matrix fracture and fiber debonding reach a certain amount, the acoustic emission cumulative energy three begins to rise, that is, a single fiber fracture occurs;
[0064] The acoustic emission cumulative energy four is the result of continuous stretching of the composite material, and the acoustic emission cumulative energy three continues to rise, corresponding to a certain amount of single fiber breakage, fiber slippage, and the beginning of a failure point. Within a few seconds after the failure point appears, only the acoustic emission cumulative energy four corresponding to the composite material fiber being pulled out appears and continues to increase.
[0065] Furthermore, the specific steps of optimizing the preparation conditions of step S1 according to the judgment result and the damage mechanism model in step S4 include:
[0066] If the judgment result shows Al 2 O 3 / Al 2 O 3 The composite material does not conform to the damage mechanism model, so find Al 2 O 3 / Al 2 O 3 The stage at which the composite material differs from the damage mechanism model, and the Al 2 O 3 / Al 2 O 3 The preparation conditions of the composite materials were optimized.
[0067] Preferably, the present invention further comprises step S5, screening of optimal preparation conditions;
[0068] Select multiple Al2O3 alloys under different preparation conditions that meet the judgment conditions of the damage mechanism model 2 O 3 / Al 2 O 3 Composite materials;
[0069] Get each Al 2 O 3 / Al 2 O 3 The composite material corresponds to the cumulative acoustic emission energy 1, the cumulative acoustic emission energy 2, the cumulative acoustic emission energy 3 and the cumulative acoustic emission energy 4. The Al corresponding to the latest cumulative acoustic emission energy 1, the cumulative acoustic emission energy 2, the cumulative acoustic emission energy 3 and the cumulative acoustic emission energy 4 are selected. 2 O 3 / Al 2 O 3 Composite materials, as the best Al 2 O 3 / Al 2 O 3 Composite materials;
[0070] The optimal Al 2 O 3 / Al 2 O 3 The preparation conditions of the composite materials were taken as the optimal preparation conditions.
[0071] In the present invention, the matrix solution, i.e., alumina slurry, is used as the raw material of the ceramic-based prepreg. The ball milling conditions affect the solid content and viscosity of the slurry, and further affect the deposition of alumina particles on the fiber. The number of fiber prepreg-hot pressing-sintering cycle processing affects the density of the fiber-reinforced ceramic-based composite material. During the drying process, the alumina particles in the slurry settle and rearrange, and the temperature and time in this process affect the performance of the material. During the sintering process, if the temperature is too low, the matrix particles in the composite material will be weakly bonded; if the temperature is too high, the fiber strength will decrease.
[0072] Compared with the prior art, the present invention has at least the following beneficial effects:
[0073] (1) The present invention uses acoustic and optical non-destructive methods to obtain time-synchronized data for cross-validation and interpretation of information related to materials and / or the structural integrity of materials, thereby improving the reliability of measurements independently recorded by acoustic emission (AE) and DIC systems and avoiding misjudgment of experimental results caused by the contingency of a single experiment;
[0074] (2) The present invention only needs to conduct one experiment to obtain reliable results; there is no need to conduct other complex and time-consuming verification experiments, which shortens the exploration period of the optimal preparation conditions, accelerates the production process of high-performance ceramic fiber reinforced ceramic matrix composites, and is conducive to the subsequent preparation of Al2O3 composites with excellent mechanical properties. 2 O 3 / Al 2 O 3 Composite materials;
[0075] (3) The present invention has a relatively clear comparison factor, which avoids subjective judgment and selection of preparation conditions through images or curves, and screens from the fundamental damage mechanism of the material, which is conducive to the preparation of Al with excellent mechanical properties. 2 O 3 / Al 2 O 3 Composite materials;
[0076] (4) The present invention uses reliable acoustic clustering results to compare key moments under different experimental conditions, thereby determining the best experimental conditions or optimizing improvement directions, providing a basis for subsequent sample manufacturing;
[0077] (5) The present invention is Al 2 O 3 / Al 2 O 3 It provides important basis and predictive evaluation means for composite material research and development, and is expected to improve research and development efficiency and significantly save experimental costs, becoming an effective auxiliary tool for research and development. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] The drawings are only for the purpose of illustrating particular embodiments and are not to be construed as limiting the invention.
[0079] Figure 1 is the Al based on the damage mechanism model in the embodiment of the present invention 2 O 3 / Al 2 O 3 Flow chart of the optimization method of composite material preparation process;
[0080] Figure 2 is the Al based on the damage mechanism model in the embodiment of the present invention 2 O 3 / Al 2 O 3 Schematic illustration of the damage mechanism model for the optimization approach to composite fabrication processes.
[0081] Figure 3 In the embodiment of the present invention, Al 2 O 3 / Al 2 O 3 Schematic diagram of DIC, mechanical curves, and acoustic emission versus time results of composite materials;
[0082] Figure 4 In the embodiment of the present invention, Al 2 O 3 / Al 2 O 3 Schematic diagram of DIC strain of composite materials;
[0083] FIG. 5( a ) is an Al 2 O 3 / Al 2 O 3 Schematic diagram of acoustic emission cluster analysis of composite materials;
[0084] FIG. 5( b ) is an Al 2 O 3 / Al 2 O 3 Schematic representation of the cumulative energy diagram of the composite material;
[0085] Figure 6 is Al in Example 2 of the present invention 2 O 3 / Al 2 O 3 Schematic diagram of acoustic emission cumulative energy diagram of composite materials;
[0086] Figure 7 is Al in Example 2 of the present invention 2 O 3 / Al 2 O 3 Schematic diagram of acoustic emission cluster analysis of composite materials;
[0087] Figure 8 is Al in Example 2 of the present invention 2 O 3 / Al 2 O 3 Schematic diagram of the DIC strain profile of the composite material;
[0088] FIG. 9( a ) is a diagram of Al in Example 2 of the present invention. 2 O 3 / Al 2 O 3 ε in the y direction of the DIC strain field diagram estimated from the crack evolution of the composite material yy Schematic diagram of the changes;
[0089] FIG. 9( b ) is a diagram of Al in Example 2 of the present invention. 2 O 3 / Al 2 O 3 ε in the x direction of the DIC strain field diagram estimated from the crack evolution of the composite material yy Schematic diagram of the changes. DETAILED DESCRIPTION
[0090] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In addition, the present invention can also be implemented in other ways different from those described herein, and therefore, the protection scope of the present invention is not limited by the specific embodiments disclosed below.
[0091] A specific embodiment of the present invention, as Figure 1 -9, discloses an Al based damage mechanism model 2 O 3 / Al 2 O 3 Optimization method of composite material preparation process, in order to illustrate the effectiveness of the method proposed by the present invention, the above technical solution of the present invention is described in detail below through a specific embodiment, and the specific implementation steps are as follows:
[0092] The present invention provides an Al based damage mechanism model 2 O 3 / Al 2 O 3 The optimization method of composite material preparation process includes:
[0093] S1. Set preparation conditions, and prepare Al according to the preparation conditions. 2 O 3 / Al 2 O 3 Composite materials;
[0094] S2, using the synchronous test system to test the A1 in step S1 2 O 3 / Al 2 O 3 The composite material is subjected to tensile test, and the acoustic emission signal and strain data are collected to obtain the corresponding acoustic emission signal cluster analysis results and strain analysis results;
[0095] S3, establishing a damage mechanism model; judging the acoustic emission signal cluster analysis results and the strain analysis results in step S2 according to the damage mechanism model to obtain a judgment result;
[0096] S4. Optimize the preparation conditions of step S1 according to the judgment result and the damage mechanism model.
[0097] Preferably, the preparation of Al in step S1 2 O 3 / Al 2 O 3 The specific steps of composite materials include:
[0098] Step S11, mixing aluminum oxide powder and deionized water, adding nitric acid, and then using a ball mill to disperse the mixture to obtain a matrix solution;
[0099] Step S12, pre-impregnating the alumina fiber cloth in the matrix solution under vacuum conditions to obtain a prepreg;
[0100] Step S13, hot pressing the prepreg under vacuum conditions to obtain a preform;
[0101] Step S14: sintering the preform to obtain the first processed Al 2 O 3 / Al 2 O 3 Composite materials;
[0102] Step S14, let t=1, t=1 indicates the first processing; t is an integer;
[0103] Step S15: Under vacuum conditions, the Al 2 O 3 / Al 2 O 3 Composite material A t Pre-impregnated in the matrix solution in step S11 to obtain a pre-impregnated body S t ;
[0104] Step S16: Under vacuum conditions, the prepreg S t Perform hot pressing and drying to obtain preform Y t ;
[0105] Step S17: t Sintering is performed to obtain the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 ;
[0106] Step S18: Determine the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 Is the mass growth of ≤1%? If so, terminate the processing and obtain the Al processed for the t+1th time 2 O 3 / Al 2 O 3 Composite material A t+1 ; If not, set t=t+1 and return to step S15.
[0107] Furthermore, the preparation conditions in step S1 include ball milling conditions, processing times, drying temperature of hot pressing, drying time of hot pressing, sintering temperature and / or sintering time;
[0108] Furthermore, the rotation speed of the ball mill is: 200-800r / h;
[0109] Furthermore, the mass ratio of the nitric acid to the alumina powder is: 0.3:40-70;
[0110] Furthermore, the mass percentage of nitric acid in step S11 is 0.3wt%;
[0111] The mass percentage of aluminum oxide powder is: 40-70wt%;
[0112] Further, the ratio of the drying temperature in step S13 to the sintering temperature in step S14 is: 12-15:100-120;
[0113] The ratio of the pre-impregnation time in step S12, the drying time in step S13 and the sintering time in step S14 is: 4-6:2-3:1;
[0114] Furthermore, the drying temperature of the hot pressing molding in step S13 is 120-150° C. and the drying time is 2-3 hours;
[0115] Furthermore, the pre-immersion time in step S12 is 4-6 hours;
[0116] The sintering temperature in step S14 is 1000-1200° C. and the sintering time is 1 hour.
[0117] The Al prepared in step S1 of the present invention 2 O 3 / Al 2 O 3 The composite material has uniform composition, excellent tensile properties, excellent morphology, and a controllable and simple preparation method, which is conducive to repeated tensile experiments.
[0118] Preferably, the synchronous testing system in step S2 includes a mechanical stretching machine, an acoustic emission testing system and a DIC system;
[0119] Furthermore, the synchronous testing system in step S2 further includes a computer;
[0120] The mechanical stretching machine, the acoustic emission test system and the DIC system are respectively connected to a computer; when the synchronous test system performs a tensile test on the sample, the evolution law of the acoustic emission signal over time and the evolution information of the DIC strain field over time and the stress-strain curve are synchronously recorded;
[0121] The mechanical stretching machine is used to apply a tensile load and record the tensile load and displacement data during the test;
[0122] The acoustic emission test system is used to obtain acoustic emission signals during the test and perform acoustic emission parameter analysis;
[0123] Furthermore, the DIC system is used to obtain the evolution information of the strain field on the material surface during the test; the DIC system includes a strain gauge for recording strain data.
[0124] The present invention uses time synchronization of data obtained by acoustic and optical non-destructive methods to cross-validate and interpret information related to materials and / or the structural integrity of materials, thereby improving the reliability of measurements independently recorded by two systems, acoustic emission (AE) and DIC systems, avoiding comparison based on only one experimental result, thereby avoiding misjudgment of experimental results due to the contingency brought about by a single experiment.
[0125] Preferably, the specific steps of obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results in step S2 include:
[0126] Use the synchronous test system to test the Al in step S1 2 O 3 / Al 2 O 3 The composite material is subjected to a tensile test. During the tensile process, acoustic emission signals are collected and DIC strain fields are photographed. Acoustic emission signals and strain data are collected at the same time. After the tensile test, corresponding acoustic emission signal cluster analysis results and strain analysis results are obtained based on the collected acoustic emission signals and strain data.
[0127] Furthermore, the acoustic emission signal cluster analysis result in step S2 includes: stage signal one, stage signal two, stage signal three and stage signal four.
[0128] Further, in step S2, the synchronous test system is used to test the A1 in step S1. 2 O 3 / Al 2 O 3 The specific steps of conducting a tensile test on a composite material, collecting acoustic emission signals and strain data, and obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results include:
[0129] Step 1. Set the stretching rate, and use the synchronous testing system to test the Al 2 O 3 / Al 2 O 3The composite material is stretched, and the composite material is subjected to elastic deformation, and a stage signal 1 is obtained; based on the stage signal 1, an acoustic emission cumulative energy 1 and a stage 1 DIC strain distribution are obtained;
[0130] The stage signal 1 includes an acoustic emission signal 1;
[0131] When the composite material undergoes elastic deformation, the acoustic emission signal 1 appears as a no-acoustic emission signal; the acoustic emission cumulative energy 1 corresponding to the no-acoustic emission signal is almost 0;
[0132] Step 2. Based on step 1, 2 O 3 / Al 2 O 3 The composite material continues to stretch, Al 2 O 3 / Al 2 O 3 The matrix of the composite material is damaged and the fiber slips, and a second stage signal is obtained; based on the corresponding second stage signal, the second acoustic emission cumulative energy and the second stage DIC strain distribution are obtained;
[0133] The second stage signal includes the first acoustic emission signal and / or the second acoustic emission signal.
[0134] The acoustic emission signal 1 is manifested as matrix cracking; the acoustic emission signal 2 is manifested as fiber debonding;
[0135] Step 3. Based on step 2, 2 O 3 / Al 2 O 3 The composite material continues to be stretched to obtain a corresponding stage signal three; based on the stage signal three, the acoustic emission cumulative energy three and the stage three DIC strain distribution are obtained;
[0136] The stage signal three includes the acoustic emission signal one and / or the acoustic emission signal two and / or the acoustic emission signal three; the acoustic emission signal three is manifested as a single fiber break;
[0137] Step 4. Based on step 3, 2 O 3 / Al 2 O 3 The composite material continues to be stretched to obtain a corresponding stage signal four; based on the stage signal four, the acoustic emission cumulative energy four and the stage four DIC strain distribution are obtained;
[0138] The stage signal four includes the acoustic emission signal one and / or the acoustic emission signal two and / or the acoustic emission signal three and / or the acoustic emission signal four; the acoustic emission signal four indicates the breakage of the fiber bundle;
[0139] Preferably, the establishment of the damage mechanism model in step S3 specifically includes: 2 O 3 / Al 2 O 3 The damage mechanism model is established based on the acoustic emission signal and DIC strain field changes corresponding to the idealized process of composite material damage.
[0140] Preferably, the damage mechanism model described in step S3 specifically includes: collecting Al 2 O 3 / Al 2 O 3 Acoustic emission signals and strain data during tensile tests of composite materials are obtained to obtain corresponding acoustic emission signal cluster analysis results and strain analysis results; further, the damage mechanism model described in step S3 includes: stage one, acoustic emission cumulative energy one appears, the acoustic emission cumulative energy one is normalized, and the DIC strain field shows a uniform strain distribution;
[0141] It can be understood that the stage 1 specifically includes: obtaining the acoustic emission cumulative energy 1 according to the received acoustic emission signal 1. Since the composite material is in the elastic deformation stage and is almost undamaged, the corresponding acoustic emission cumulative energy 1 is very low. At the same time, the DIC strain field exhibits a uniform strain distribution;
[0142] In stage 2, the acoustic emission cumulative energy 2 appears and begins to increase, and at the same time, the corresponding DIC strain bands no longer show uniform strain bands;
[0143] In stage three, the acoustic emission cumulative energy 2 continues to increase to its corresponding boundary point, and the acoustic emission cumulative energy 3 appears. The acoustic emission cumulative energy 3 begins to climb and enters the high strain stage, and a stress concentration point appears in the DIC strain field;
[0144] Furthermore, the stage three also includes the acoustic emission cumulative energy three and the acoustic emission signal two synchronously rising in a fluctuating manner;
[0145] In stage four, the acoustic emission cumulative energy three climbs to the corresponding boundary point, and a failure point appears. After a certain period of time, the acoustic emission signal two caused by fiber pull-out appears, and the acoustic emission cumulative energy four corresponding to it continues to increase, and the DIC stress concentration point continues to expand until it is destroyed.
[0146] It can be understood that the cumulative acoustic emission energy of the composite material is at the beginning of stretching. According to the elasticity of the composite material itself, the composite material at the current stage has no damage, and the corresponding cumulative acoustic emission energy is almost 0;
[0147] The second acoustic emission cumulative energy is that the composite material is continuously stretched, and the composite material begins to break the matrix and the fibers begin to debond, and the corresponding second acoustic emission cumulative energy begins to increase;
[0148] The acoustic emission cumulative energy three is to continue to stretch the composite material. When the acoustic emission cumulative energy two reaches a certain critical point, the matrix fracture and fiber debonding reach a certain amount, the acoustic emission cumulative energy three begins to rise, that is, a single fiber fracture occurs;
[0149] The acoustic emission cumulative energy four is the result of continuous stretching of the composite material, and the acoustic emission cumulative energy three continues to rise, corresponding to a certain amount of single fiber breakage, fiber slippage, and the beginning of a failure point. Within a few seconds after the failure point appears, only the acoustic emission cumulative energy four corresponding to the composite material fiber being pulled out appears and continues to increase.
[0150] Furthermore, the specific steps of optimizing the preparation conditions of step S1 according to the judgment result and the damage mechanism model in step S4 include:
[0151] If the judgment result shows Al 2 O 3 / Al 2 O 3 The composite material does not conform to the damage mechanism model, so find Al 2 O 3 / Al 2 O 3 The stage at which the composite material differs from the damage mechanism model, and the Al 2 O 3 / Al 2 O 3 The preparation conditions of the composite materials were optimized.
[0152] Preferably, the present invention further comprises step S5, screening of optimal preparation conditions;
[0153] Select multiple Al2O3 alloys under different preparation conditions that meet the judgment conditions of the damage mechanism model 2 O 3 / Al 2 O 3 Composite materials;
[0154] Get each Al 2 O 3 / Al 2 O 3 The composite material corresponds to the cumulative acoustic emission energy 1, the cumulative acoustic emission energy 2, the cumulative acoustic emission energy 3 and the cumulative acoustic emission energy 4. The Al corresponding to the latest cumulative acoustic emission energy 1, the cumulative acoustic emission energy 2, the cumulative acoustic emission energy 3 and the cumulative acoustic emission energy 4 are selected. 2 O 3 / Al 2 O 3 Composite materials, as the best Al2 O 3 / Al 2 O 3 Composite materials;
[0155] The optimal Al 2 O 3 / Al 2 O 3 The preparation conditions of the composite materials were taken as the optimal preparation conditions.
[0156] Embodiment 1:
[0157] Preparation of alumina slurry: Alumina powder and deionized water are mixed, 0.3wt% nitric acid is added, and then dispersed in a ball mill at a speed of 400r / h for 2h to obtain a matrix solution; under vacuum conditions, a 18cm*6cm single-layer alumina fiber cloth is pre-impregnated in the above-mentioned matrix solution for 5h to obtain a prepreg; under vacuum conditions, the prepreg is hot-pressed at 150°C for 2h to obtain a preform; the preform is sintered at 1000°C for 1h to obtain the alumina / alumina composite material; the fiber pre-impregnation-hot-pressing-sintering steps are repeated until the mass increase of the alumina / alumina composite material does not exceed 1%, then the cycle is terminated to obtain the sample.
[0158] The specimens were subjected to tensile tests for mechanical property testing. During the entire tensile process, acoustic emission signals were collected and clustered, and DIC strain measurement and analysis were performed simultaneously. The results are shown in Figure 2. Figure 3 -As shown in Figure 5, the damage process of the sample is:
[0159] The first stage: 0-50s, the beginning time, normalized cumulative energy, DIC strain field can also reflect;
[0160] The second stage: 50-70s, the accumulated energy begins to increase, strain bands can also be seen in DIC, and stress concentration occurs;
[0161] The third stage: 70-140s, the accumulated energy changes from slow to fast and then to slow again, and DIC reflects that large but not catastrophic damage occurs at this time;
[0162] The fourth stage: 140s-failure, DIC reflects more damage, and the final accumulated energy rises in a "step-by-step" manner. Combined with the previous acoustic emission cluster analysis, it is caused by the breakage of a large number of single fibers and the shedding of the closely contacted matrix.
[0163] Comparing the above damage process with the damage mechanism model, it can be obtained that starting from the third stage, the strain curve and the accumulated energy do not conform to the process of the damage mechanism model. The damage of the sample mainly comes from the cracking of the matrix and the breakage and detachment of single fibers in sequence. Therefore, it is necessary to optimize and improve the preparation conditions, consider improving the ball milling conditions, and appropriately extend the hot pressing time to increase the matrix density and reduce the sample damage caused by matrix cracking during the stretching process.
[0164] Embodiment 2:
[0165] The preparation conditions of the sample of Example 1 were optimized. The sample was prepared under the following preparation conditions:
[0166] Preparation of alumina slurry: Alumina powder and deionized water are mixed, 0.3wt% nitric acid is added, and then dispersed in a ball mill at a speed of 500r / h for 3 hours to obtain a matrix solution; under vacuum conditions, a single layer of alumina fiber cloth is pre-impregnated in the above matrix solution for 5 hours to obtain a prepreg; under vacuum conditions, the prepreg is hot-pressed at 130°C for 3 hours to obtain a preform; the preform is sintered at 1100°C for 1 hour to obtain the alumina / alumina composite material; the fiber pre-impregnation-hot-pressing-sintering steps are repeated until the mass increase of the alumina / alumina composite material does not exceed 1%, then the cycle is terminated to obtain the sample.
[0167] The specimens were subjected to tensile tests for mechanical property testing. During the entire tensile process, acoustic emission signals were collected and clustered, and DIC strain measurement and analysis were performed simultaneously. The results are shown in Figure 2. Figure 6-Figure 8 As shown in Figure 2, the damage process of the sample is:
[0168] The first stage: 0-40s (0 to point A), at the beginning, the accumulated energy is normalized and the DIC strain field shows a uniform strain distribution;
[0169] The second stage: 40-160s (points A to C), the accumulated energy begins to increase, strain bands can also be seen by DIC, and stress concentration occurs;
[0170] The third stage: 160-270s (point C to E), with point C as the dividing point, the cumulative energy climbs and enters the high strain stage. The cumulative energy in acoustic emission and fiber debonding fluctuate and rise synchronously. Fiber debonding is the main toughening mechanism, and stress concentration points appear in DIC.
[0171] The fourth stage: 270s-failure (after point E), accompanied by the slip of the fiber, the acoustic emission shows that within a few seconds after the failure point, other damage signals have stopped, only the fiber pullout corresponds to the continuous increase of accumulated energy, and the DIC stress concentration point continues to expand until it is destroyed.
[0172] The above damage process is consistent with the damage mechanism model, so the sample is valid and the optimization effect is more obvious. The uniformly distributed and well-deposited alumina slurry can weaken the stress concentration at the interface and effectively induce toughening mechanisms such as crack deflection, fiber debonding, and slip pull-out. The optimized strain curve and accumulated energy are consistent with the law of composite material damage.
[0173] Furthermore, the mechanism of crack initiation is understood, as shown in Figure 9, the DIC strain field is constructed; for the position x=5, the ε in the vertical direction is obtained by the DIC analysis software. yy By changing the vertical position of the loading crack, the crack appears at y = 20, and the horizontal ε yy It is found that the crack initiates from the leftmost side (x=1), expands and finally breaks down.
[0174] Furthermore, if the sample is valid, compare the first dividing point appearance time and the failure point appearance time of the sample under different experimental conditions. When the first dividing point time and the failure point time are later than those under other experimental conditions, the preparation conditions of the sample are the optimal preparation conditions under the same material.
[0175] The present invention can obtain reliable results by only conducting one experiment on the sample; it screens from the root of the material damage mechanism, without the need for complex and time-consuming other verification experiments (such as microstructure analysis, etc.), and uses reliable acoustic clustering results to compare the key moments under different experimental conditions, so as to judge the best experimental conditions or optimize the improvement direction, thereby shortening the preparation process optimization process and facilitating the subsequent preparation of high-performance Al 2 O 3 / Al 2 O 3 Composite materials provide a basis for improving R&D efficiency and significantly saving experimental costs, becoming an effective auxiliary tool for R&D.
[0176] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on a damage mechanism model, characterized in that: include: S1. Setting preparation conditions, and preparing an Al2O3 / Al2O3 composite material according to the preparation conditions; S2, using a synchronous testing system to perform a tensile test on the Al2O3 / Al2O3 composite material described in step S1, collecting acoustic emission signals and strain data, and obtaining corresponding acoustic emission signal cluster analysis results and strain analysis results; S3, establishing a damage mechanism model; judging the acoustic emission signal cluster analysis results and the strain analysis results in step S2 according to the damage mechanism model to obtain a judgment result; S4. Optimize the preparation conditions of step S1 according to the judgment result and the damage mechanism model.
2. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 1, characterized in that: The specific steps of preparing the Al2O3 / Al2O3 composite material in step S1 include: Step S11, mixing aluminum oxide powder and deionized water to obtain a matrix solution; Step S12, pre-impregnating the alumina fiber cloth in the matrix solution to obtain a prepreg; Step S13, hot pressing the prepreg to obtain a preform; Step S14, sintering the preform to obtain a first processed Al2O3 / Al2O3 composite material; Step S14, let t = 1, t = 1 represents the first processing; Step S15: The Al2O3 / Al2O3 composite material A processed for the tth time t Pre-impregnated in the matrix solution in step S11 to obtain a pre-impregnated body S t ; Step S16: t Perform hot pressing and drying to obtain preform Y t ; Step S17: t Sintering is performed to obtain the Al2O3 / Al2O3 composite material A processed for the t+1th time t+1 ; Step S18: Determine the Al2O3 / Al2O3 composite material A processed for the t+1th time t+1 Is the mass growth ≤1%? If so, the processing is terminated to obtain the Al2O3 / Al2O3 composite material A processed for the t+1th time t+1 ; If not, set t=t+1 and return to step S15.
3. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 1, characterized in that: The specific steps of obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results in step S2 include: A synchronous testing system is used to perform a tensile test on the Al2O3 / Al2O3 composite material described in step S1, and during the stretching process, acoustic emission signals are collected and DIC strain fields are photographed, and acoustic emission signals and strain data are collected at the same time, and after the stretching is completed, corresponding acoustic emission signal clustering analysis results and strain analysis results are obtained based on the collected acoustic emission signals and strain data; The synchronous testing system includes a mechanical stretching machine, an acoustic emission testing system and a DIC strain system.
4. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 1, characterized in that: The acoustic emission signal cluster analysis results include: stage signal one, stage signal two, stage signal three and stage signal four.
5. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 1, characterized in that: The specific steps of obtaining the corresponding acoustic emission signal cluster analysis results and strain analysis results in step S2 include: Step 1. Set the stretching rate, and use the synchronous testing system to stretch the Al2O3 / Al2O3 composite material according to the stretching rate. The composite material is subjected to elastic deformation, and the corresponding stage signal 1 is obtained; based on the stage signal 1, the acoustic emission cumulative energy 1 and the stage 1 DIC strain distribution are obtained; Step 2. Based on step 1, the Al2O3 / Al2O3 composite material is further stretched, the matrix of the Al2O3 / Al2O3 composite material is damaged, the fiber slips, and a stage signal 2 is obtained; based on the stage signal 2, the acoustic emission cumulative energy 2 and the stage 2 DIC strain distribution are obtained; Step 3. Based on step 2, the Al2O3 / Al2O3 composite material is further stretched to obtain the corresponding stage signal three; based on the stage signal three, the acoustic emission cumulative energy three and the stage three DIC strain distribution are obtained; Step 4. Based on step 3, the Al2O3 / Al2O3 composite material is continued to be stretched to obtain the corresponding stage signal four; based on the stage signal four, the acoustic emission cumulative energy four and the stage four DIC strain distribution are obtained.
6. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 5, characterized in that: The stage signal 1 includes acoustic emission signal 1; the stage signal 2 includes acoustic emission signal 1 and / or acoustic emission signal 2; The stage signal three includes acoustic emission signal one and / or acoustic emission signal two and / or acoustic emission signal three; The stage signal four includes acoustic emission signal one and / or acoustic emission signal two and / or acoustic emission signal three and / or acoustic emission signal four.
7. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 6, characterized in that: The acoustic emission signal 1 is manifested as matrix cracking; the acoustic emission signal 2 is manifested as fiber debonding; The acoustic emission signal three is manifested as a single fiber breakage; The acoustic emission signal 4 indicates fiber bundle breakage.
8. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 5, characterized in that: The damage mechanism model in step S3 includes: In stage 1, the acoustic emission cumulative energy is 1, and the acoustic emission cumulative energy is normalized to 1, and the DIC strain field shows a uniform strain distribution; In stage 2, the acoustic emission cumulative energy 2 appears and begins to increase, and at the same time, the corresponding DIC strain bands no longer show uniform strain bands; In stage three, the acoustic emission cumulative energy 2 continues to increase to its corresponding boundary point, and the acoustic emission cumulative energy 3 appears. The acoustic emission cumulative energy 3 begins to climb and enters the high strain stage, and a stress concentration point appears in the DIC strain field; In stage four, the acoustic emission cumulative energy three climbs to the corresponding boundary point, and a failure point appears. After a certain period of time, the acoustic emission signal two caused by fiber pull-out appears, and the acoustic emission cumulative energy four corresponding to it continues to increase, and the DIC stress concentration point continues to expand until it is destroyed.
9. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 8, characterized in that: The specific steps of optimizing the preparation conditions of step S1 according to the judgment result and the damage mechanism model in step S4 include: If the judgment result shows that the Al2O3 / Al2O3 composite material does not conform to the damage mechanism model, the stage at which the Al2O3 / Al2O3 composite material differs from the damage mechanism model is found, and the preparation conditions of the Al2O3 / Al2O3 composite material are optimized according to the stage at which the difference occurs.
10. The method for optimizing the preparation process of Al2O3 / Al2O3 composite materials based on the damage mechanism model according to claim 9, characterized in that: The process also includes step S5, screening of optimal preparation conditions; Select multiple Al2O3 / Al2O3 composite materials under different preparation conditions that meet the judgment conditions of the damage mechanism model; Obtain the appearance time of the first, second, third and fourth acoustic emission cumulative energies of each Al2O3 / Al2O3 composite material; select the Al2O3 / Al2O3 composite material corresponding to the latest appearance time of the first, second, third and fourth acoustic emission cumulative energies of the acoustic emission as the best Al2O3 / Al2O3 composite material; The preparation conditions of the optimal Al2O3 / Al2O3 composite material are taken as the optimal preparation conditions.
Citation Information
Patent Citations
Method for achieving process optimization by simulating magnesium alloy equal channel angular extrusion
CN107413870A
Preparation method and application of alumina fiber reinforced alumina ceramic-based composite material
CN113651627A
Self-adaptive control method for hole making damage of carbon fiber reinforced composite material
CN114609906A
Simulation evaluation method for mechanical property attenuation of turbine blade in full-area corrosion environment
CN114705534A
Process optimization method and system for improving performance of aviation composite material
CN117238421A
